Optical Interferometric Corrosion Protection Evaluation of a Coated Copper in Sulphate/Chloride Solution - Mayorga, Darwin; Uribe, Diego; Guardian, Rene; Menchaca-Campos, Carmina; Uruchurtu, Jorge (Innovations in Corrosion and Materials Science (Discontinued), 2017)
Background: Optical interferometry based methods have been used to monitor electrochemical corrosion and protection processes. Quantitative and qualitative information related to these processes, is obtained by using a Michelson interferometer technique configuration. This technique without the need of direct physical contact with the sample during reaction time is based on a simple inspection of intensity patterns. Methods: Evaluation of corrosion phenomenon of bare copper corrosion protection by ABS (Acrylonitrile- butadiene-styrene) coating using Michelson interferometry, was obtained. Bare and coated samples were exposed to different conditions in chloride solution and immersed as a function of time, and electrochemical noise and impedance methods and interferometric measurements were obtained and correlated. Results: Experimental results suggest important kinetic information regarding copper corrosion and coating protection performance taking place, corroborated and correlated with electrochemical methods. Interferometric measurements reflect the changing corrosion conditions and coating performance. Conclusions: Good corrosion protection of ABS coating performance through the Michelson interferometric technique was demonstrated.
Keywords: electrochemical corrosion